Cartography : Navigating a Year in Iraq - Schifani, Katherine (Book collections on Project MUSE., 2022)
"Cartography" is the story of Katherine Schifani's experience as a gay woman serving as a counterterrorism advisor in Iraq in 2011, surrounded by strangers and strangeness amid the repeal of the military's Don't Ask, Don't Tell policy"--